2016
DOI: 10.1021/acs.jpclett.5b02547
|View full text |Cite
|
Sign up to set email alerts
|

Entangled Electrons Foil Synthesis of Elusive Low-Valent Vanadium Oxo Complex

Abstract: We examine the recently reported first synthesis of the elusive low-valent vanadium(III) in a vanadium oxo complex with a computation representing 10(21) quantum degrees of freedom. While this computation is intractable with a conventionally constructed wave function, it is performed here by a direct calculation of the system's two-electron reduced density matrix (2-RDM), where the 2-RDM is constrained by nontrivial conditions, known as N-representability conditions, that restrict the 2-RDM to represent an N e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 42 publications
1
63
0
Order By: Relevance
“…[19][20][21] Recent studies involving ligand non-innocence in manganese porphyrins and vanadium oxo complexes have shown that methods that fail to capture multireference electron correlation can mistakenly attribute a redox event to being metal-centered. [22][23][24] In separate studies on polyaromatic hydrocarbons, multireference correlation was found to give rise to increasing polyradical character with increasing size for both linear chains and two-dimensional geometries. 25 In this work, we study strong electron correlation in FeMoco using two multireference methods: the configuration interaction complete-active-space self-consistent-field (CI-CASSCF) method 26,27 and the variational two-electron reduced density matrix (V2RDM) method.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Recent studies involving ligand non-innocence in manganese porphyrins and vanadium oxo complexes have shown that methods that fail to capture multireference electron correlation can mistakenly attribute a redox event to being metal-centered. [22][23][24] In separate studies on polyaromatic hydrocarbons, multireference correlation was found to give rise to increasing polyradical character with increasing size for both linear chains and two-dimensional geometries. 25 In this work, we study strong electron correlation in FeMoco using two multireference methods: the configuration interaction complete-active-space self-consistent-field (CI-CASSCF) method 26,27 and the variational two-electron reduced density matrix (V2RDM) method.…”
Section: Introductionmentioning
confidence: 99%
“…Standard CASSCF techniques are limited by computational costs to modest-sized systems, for example, for closed-shell singlets, to the treatment of no more than approximately 18 electrons in 18 active orbitals, but the treatment of larger active spaces is possible through the use of GASSCF or other MCSCF methods, including restricted active space self-consistent field (RASSCF), 15 occupation-restricted multiple active space (ORMAS), 16 splitGAS, 17,18 stochastic CASSCF approaches, 19 density matrix renormalization group (DMRG), [20][21][22] and the variational 2-RDM method. [23][24][25] One kind of post-SCF correction (step (ii)) is multireference second-order perturbation theory (MR-PT2), which can be used with a number of reference wave functions including CASSCF, which yields CASPT2, 26 RASSCF, which yields RASPT2, 27 and GASSCF, which yields GASPT2. 28 Another kind of post-SCF treatment, which is the main subject of the present paper, is MC-PDFT.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum signature developed here, the large eigenvalue of the (modified) particle-hole matrix [25][26][27][28][29] , is present if and only if the fermion system exhibits condensation of particle-hole pairs (excitons) into a global state-exciton condensation. It allows us to predict the existence and extent of exciton condensation in any quantum system from only an electronic structure calculation of the two-electron reduced density matrix (2-RDM) [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . While this definition includes various phase transitions involving condensates of soft phonons that are not conventionally viewed in these terms, such disruptive transitions, as explained by Kohn and Sherrington 45 , can be relevantly viewed in the context of exciton condensation.…”
mentioning
confidence: 99%
“…Non-trivial direct calculations of the two-electron reduced density matrix (2-RDM) capture strong electron correlation including the long-range order of the exciton condensation. Such calculations, cited by the National Research Council in 1995 as one of the top outstanding problems in physical science, have only become possible recently [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and correspond to wavefunction calculations where the wavefunction, if constructible as a combination of determinants, would require a billion times the degrees of freedom treatable today by stateof-the-art supercomputers. Molecular-scale condensates, screened by electronic structure calculations, may be useful for the development of dissipationless molecular circuits and devices, especially in the context of molecular electronics.…”
mentioning
confidence: 99%
See 1 more Smart Citation